Perioperative Pulmonary Circulatory Changes During Bilateral Total Hip Arthroplasty Under Regional Anesthesia. Issue 5 (1st August 2010) - Memtsoudis, Stavros G.; Salvati, Eduardo A.; Go, George; Ma, Yan; Sharrock, Nigel E.
Abstract : Background and Objectives: The transient and rarely clinically relevant effect of bone and cement embolization during unilateral joint arthroplasty is a known phenomenon. However, available studies do not address events surrounding bilateral total hip arthroplasties, during which embolic load is presumably doubled. To elucidate events surrounding this increasingly used procedure and assess the effect on the pulmonary hemodynamics in the intraoperative and postoperative periods, we studied 24 subjects undergoing cemented bilateral total hip arthroplasty during the same anesthetic session. Materials: Twenty-four patients without previous pulmonary history undergoing cemented bilateral total hip arthroplasty under controlled epidural hypotension were enrolled. Pulmonary artery catheters were inserted and hemodynamic variables were recorded at baseline, 5 mins after the implantation of each hip joint, 1 hr and 1 day after surgery. Mixed venous blood gases and complete blood counts were analyzed at every time point. Results: An increase in pulmonary vascular resistance was observed after the second but not the first hip implantation when compared with values at incision. Pulmonary vascular resistance remained elevated 1 hr after surgery. Pulmonary artery pressures were significantly elevated on postoperative day 1 compared with those at baseline. The white blood cell count increased in response to the second hip implantation but not the first compared with incision. Conclusions: The embolization of material during bilateral total hip arthroplasty is associated with prolonged increases in pulmonary artery pressures and vascular resistance, particularly after completion of the second side. Performance of bilateral procedures should be cautiously considered in patients with diseases suggesting decreased right ventricular reserve.